1998
DOI: 10.1080/010503998422674
|View full text |Cite
|
Sign up to set email alerts
|

Average Thresholds in the 8 to 20 kHz Range in Young Adults

Abstract: The sound-pressure level thresholds in the extended high-frequency range (8 to 20 kHz) were measured in 25 non-hearing-impaired young adults from 20 to 29 years of age. The result was not unlike that obtained by previous investigators; the thresholds increased gradually as a function of frequency. However, two notable points were found: one that the threshold reached a plateau above 18 kHz, and the other that it decreased slightly at 12 kHz. As the subjects might respond to the low-frequency noise of the stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 4 publications
4
17
1
2
Order By: Relevance
“…Auditory sensitivity in dBNA improved as a function of increased frequency, 23 partially in disagreement with literature results. 10 Results in this study showed better sensitivity at higher frequencies in young individuals, with a reduction 21 this is probably due to the maximum output limit of the audiometer (60 dBNA at 12.5kHz and 40 dBNA at 16kHz). However, the importance of the 12.5kHz frequency in separating groups by age, seen in our study, is consistent with data presented in other papers.…”
Section: Age Effectmentioning
confidence: 51%
See 2 more Smart Citations
“…Auditory sensitivity in dBNA improved as a function of increased frequency, 23 partially in disagreement with literature results. 10 Results in this study showed better sensitivity at higher frequencies in young individuals, with a reduction 21 this is probably due to the maximum output limit of the audiometer (60 dBNA at 12.5kHz and 40 dBNA at 16kHz). However, the importance of the 12.5kHz frequency in separating groups by age, seen in our study, is consistent with data presented in other papers.…”
Section: Age Effectmentioning
confidence: 51%
“…Studies of young individuals with no hearing loss 10 showed significant threshold (dBNPS) increases at 12kHz and above, and reduced thresholds at 20kHz. Auditory sensitivity in dBNA improved as a function of increased frequency, 23 partially in disagreement with literature results.…”
Section: Age Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Above 20 kHz, however, thresholds increased less rapidly. Sakamoto et al [12] who measured hearing thresholds up to 20 kHz also reported that the threshold reached a plateau above 18 kHz. Although the mechanisms responsible for detection of ultrasounds are not specified, it can be said that the threshold above 22 kHz is higher than 85 dB SPL and the threshold increases less rapidly between about 18 kHz and 24 kHz.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, it would be valuable to evaluate the influences in terms of the absolute threshold of hearing. Absolute thresholds for pure tones have been studied by many research groups [5][6][7][8][9][10][11][12][13]. These studies show that the absolute threshold starts to increase sharply when the signal frequency exceeds about 15 kHz; it reaches 80 dB SPL at the frequency of 20 kHz [5,8,10,13].…”
Section: Introductionmentioning
confidence: 99%